Potential activity of Ferula macrecolea essential oil for treating Giardia lamblia infection through modulating electrolytes and suppressing NF-κB p65 pathway - Salimikia, Iraj; Yaghoubi, Seyed Ehsan; Khalaf, Amal Khudair; Masoori, Leila; Ghasemian Yadegari, Javad; Mahmoudvand, Hossein (Frontiers in Pharmacology, 2025)
BackgroundThe pharmacological treatment of Giardia lamblia infection involves the use of chemical agents, such as metronidazole (MNZ). However, these medications are associated with a range of adverse effects, and their effectiveness is not definitively established. In light of the previously discussed information and the recognized antimicrobial properties of Ferula macrecolea, this study aims to investigate both the in vitro and in vivo anti-giardial effects of F. macrecolea essential oil (FME) on G. lamblia infection.MethodsGas chromatography-mass spectrometry (GC-MS) was utilized to analyze the chemical composition of the prepared FME. The MTT colorimetric assay was employed to assess FME’s in vitro anti-giardial and cytotoxic activities. FME’s in vivo effects were evaluated compared to MNZ in mice infected with G. lamblia. Additionally, the effects of FME therapy on serum electrolyte levels and the expression levels of inflammatory cytokines were assessed.ResultsThe primary components of FME were identified as terpinolene (78.72%), n-nonanal (4.47%), and linalool (4.35%). FME significantly reduced the viability and growth rate of G. lamblia trophozoites (IC50 = 21.6 μg/mL) and cysts (IC50 = 27.6 μg/mL) in a dose-dependent manner compared to the control group (p < 0.001). The CC50 value for FME against normal intestinal cells was determined to be 207.4 μg/mL. In vivo, assays demonstrated that the administration of various doses of FME, particularly in combination with MNZ over 7 days, resulted in a statistically significant reduction in the mean number and viability of Giardia cysts, serum level electrolytes (sodium and potassium), and the expression levels of interleukin-1 (IL-1), tumor necrosis factor-alpha (TNF-α), nuclear factor κB p65 (NF-κB p65), and Toll-like receptor 4 (TLR-4) in mice with giardiasis (p < 0.001).ConclusionThis study’s results demonstrate the extract’s efficacy in vitro against G. lamblia, exhibiting minimal cytotoxicity towards normal cells. Furthermore, the extract was shown to manage giardiasis in murine models by modulating electrolyte levels and inflammatory responses via suppressing the NF-κB p65/TLR pathways. However, further research is necessary to clarify the specific efficacy and mechanisms of action of the extract in combating G. lamblia infection.